Rational design and tailoring of imprinted polymeric enantioselective sensor layered on multiwalled carbon nanotubes for the chiral recognition of d-mandelic acid. Issue 39 (19th September 2019) - Sajini, T.; John, Sam; Mathew, Beena
Abstract : Attempts have been made to investigate the feasibility of fabricating an enantiomeric sensor for the specific detection of d -mandelic acid layered on vinyl-MWCNT using molecular imprinting technology. Abstract : Attempts have been made to investigate the feasibility of fabricating an enantiomeric sensor for the selective and specific detection of d -mandelic acid (d -MA) layered on vinyl-functionalized multiwalled carbon nanotubes (vinyl-MWCNT) using an exploratory technique of molecular imprinting. Here computational strategies have been applied to design a composite of molecular imprinted polymers using d -MA, exhibiting a significant role in pharmaceutical synthetic industry, as a template molecule. Effects of functional monomer, cross-linker and template-monomer mole ratio were determined computationally using density functional theory calculations with B3LYP functional and generic 6-31G (d, p) basis set. The enantioselective sensor is fabricated on a platinum working electrode using imprinted and non-imprinted polymers and electrochemical features are investigated using electrochemical measurements such as cyclic voltammetry, differential pulse voltammetry and electrochemical impedance spectroscopy. Several parameters including scan rate, pH of the buffer and ratio of template and functional monomer are investigated and optimized during sensor preparation. For a better assessment, non-imprinted polymer on MWCNT, which is designated as MWCNT-NIP, was fabricated using the same method, only without adding the d -MA molecule during the polymerization process. Characterizations techniques like Fourier transform infrared spectroscopy, X-ray diffraction technique, thermogravimetric analysis, scanning electron microscopy and transmission electron microscopy were used to analyze the fabricated polymer composites.